Teachersa Responsibilities in-Loco-Parentis in Secondary Schools in Abraka Metropolis, Delta State, Nigeria (Global Journal of Human-Social Science, 2012)
This paper examined teachers responsibilities inloco- parentis in secondary schools in Abraka metropolis Delta State Nigeria It high lightened some applied precedent cases of in-loco-parentis doctrine in secondary schools using variables such as experience location of school and size of school in the area of study Three research questions and three hypotheses were formulated and tested with t-test statistic The population of teachers used was 124 out of which 24 were sampled using stratified random sampling technique An instrument was constructed for data collection and the result showed that experienced teachers who have courses in school law improved their knowledge of the legal aspect of school operation in in-loco-parentis doctrine Disciplinary measures were effective in the rural schools because there was room for personal interaction The teacher s duty of governance discipline care and safety were now taken more seriously Based on the conclusions it was recommended that in service training should be organized for less experienced teachers to enable them know their rights and those of students to avoid infringement and to play their role as parents in the school system
Keywords: Teachers2019; Responsibilities; In-Loco-Parentis; Nigerian Secondary Schools